Melatonin Supplementation, a Strategy to Prevent Neurological Diseases through Maintaining Integrity of Blood Brain Barrier in Old People - Liu, Wen-Cao; Wang, Xiaona; Zhang, Xinyu; Chen, Xi; Jin, Xinchun (Frontiers in Aging Neuroscience, 2017)
Blood brain barrier (BBB) plays a crucial role in maintaining homeostasis of microenvironment that is essential to neural function of the central nervous system. When facing various extrinsic or intrinsic stimuli, BBB is damaged which is an early event in pathogenesis of a variety of neurological diseases in old patients including acute and chronic cerebral ischemia, Alzheimer’s disease and etc. Treatments that could maintain the integrity of BBB may prevent neurological diseases following various stimuli. Old people often face a common stress of sepsis, during which lipopolysaccharide (LPS) is released into circulation and the integrity of BBB is damaged. Of note, there is a significant decrease of melatonin level in old people and animal. Melatonin has been shown to preserves BBB integrity and permeability via a variety of pathways: inhibition of matrix metalloproteinase-9, inhibition of NADPH oxidase-2, and impact on silent information regulator 1 (SIRT1) and NLRP3 inflammasome. More important, a recent study showed that melatonin supplementation alleviates LPS-induced BBB damage in old mice through activating AMPK and inhibiting gp91 phox, suggesting that melatonin supplementation may help prevent neurological diseases through maintaining the integrity of BBB in old people.